(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article provides information on the reforms and effective work being carried out in Uzbekistan to increase the active participation of women in society. Besides, article has been analyzed of reforms to increase the socio-political activity of women and ensuring gender equality in Uzbekistan by the helping scientific literature